2011
DOI: 10.2174/138161211797052367
|View full text |Cite
|
Sign up to set email alerts
|

Metallodendrimers and Dendrimer Nanocomposites

Abstract: Dendrimers are polymeric compounds with highly branched structures and functionally tunable peripheral groups. Because of their low polydispersity, high degree of molecular uniformity, and precisely controlled structure, dendrimers are excellent models for demonstrating a variety of biological activities. With the attachment of metals ions and/or metals, metallodendrimers or dendrimer nanocomposites, respectively, provide diverse characters for a variety of applications. Functionalization with additional moiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…A new branch of the dendrimer studies deals with metallodendrimers having unique biological and biomedical activities. The incorporation of metal ions into the dendrimer structure opens interesting prospects for dendrimer chemistry and facilitates their enhanced biological activity [7,8]. Therefore, lately, the application of such compounds in medical chemistry as a new class of metal-containing biomolecules-has expanded significantly.…”
Section: Introductionmentioning
confidence: 99%
“…A new branch of the dendrimer studies deals with metallodendrimers having unique biological and biomedical activities. The incorporation of metal ions into the dendrimer structure opens interesting prospects for dendrimer chemistry and facilitates their enhanced biological activity [7,8]. Therefore, lately, the application of such compounds in medical chemistry as a new class of metal-containing biomolecules-has expanded significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Some biomimetic nanomaterials, such as metal oxides (Piro and Reisberg, 2017;Nikolova and Chavali, 2020), metal hydroxides (Sun et al, 2019) metallodendrimers (Tang et al, 2011), and polymers (Zhao et al, 2018;Regan et al, 2019) have also been applied as biomimetic nanomaterials for disease diagnosis; however, these nanomaterials are not discussed in this review.…”
Section: Protein-based Nanomaterialsmentioning
confidence: 99%
“…In case of their prone-to-agglomerate in solution, stabilization of NPs is of great deal. Among various stabilizers such as surfactants (11), ligands, micelles and polymers (12,13), dendrimers are promising templates to synthesize numerous transition metal NPs such as Ag (14)(15)(16), Au (14,17), Cu (18,19), Ni (20), and Ru (21) with well-regulated size, position, and composition depending on their three-dimensional, monodisperse, unique architectures preventing them from nanoparticle growth, assembly, aggregation, and damage (22,23). Thus, the size and shape of the resulting dendrimer nanocomposites (DNCs) or dendrimerencapsulated metal nanoparticles (DENs), can remain steady so that a constant desired activity can be reached.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, DNCs have been intensively prepared and characterized by using commercially available ethylene diamine core poly(amido amine) (PAMAM) cored dendrimers, and their catalytic properties were investigated (22). Results of these studies revealed that generation number and surface functional group has a crucial role on effect on the catalytic activity of DNCs.…”
Section: Introductionmentioning
confidence: 99%